Focal destructive cholangiopathy associated with amoxycillin/clavulanic acid (Augmentin). - Ryley, N; Fleming, K; Chapman, R (1995)
Amoxycillin/clavulanic acid (Augmentin) has been widely used as a broad spectrum antibiotic since its introduction in 1981, since which time a number of reports of adverse hepatic reaction to the drug combination have been published. This paper describes five patients presenting with cholestatic illness within 8 weeks of a course of amoxycillin/clavulanic acid. The clinical picture indicated a direct link between the illness and the drug combination. Hepatic histology revealed a distinctive focal destructive cholangiopathy in all five patients, which has not previously been reported. Two also showed a granulomatous reaction, which has only previously been reported in one patient. Parallels are drawn with other diseases displaying bile duct destruction, and it is suggested that immunologically mediated drug-induced biliary damage may be involved. One of the five patients developed chronic liver disease with persistence of cholestatic liver biochemical tests, which has not previously been reported. The severity of the reaction and its prolonged course merit wider recognition of the possible adverse hepatic reaction to amoxycillin/clavulanic acid.